2021
DOI: 10.1002/jcb.29886
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of hedgehog signaling network‐related gene expression in breast cancer patients

Abstract: Breast cancer continues to be a serious public health problem. The role of the hedgehog pathway in normal development of the mammary gland as well as in carcinogenesis and progression of breast cancer is the subject of intense investigation, revealing functional interactions with cell surface heparan sulfate. Nevertheless, its influence on breast cancer prognosis, and its relation to specific sulfation motifs in heparan sulfate have only been poorly studied in large patient cohorts. Using the public database K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 81 publications
(205 reference statements)
1
11
0
Order By: Relevance
“…They found that without considering subgroup of BRCA, the high expression of SHH, HHAT, GLI1, GLI2, GLI3 and PTCH1 were associated with better RFS. High expression of HHAT is associated with better OS [39]. In our study, we found that GREB1L was also a related gene of HH signaling pathway, its high expression indicated better OS and RFS of BRCA.…”
Section: Discussionsupporting
confidence: 56%
“…They found that without considering subgroup of BRCA, the high expression of SHH, HHAT, GLI1, GLI2, GLI3 and PTCH1 were associated with better RFS. High expression of HHAT is associated with better OS [39]. In our study, we found that GREB1L was also a related gene of HH signaling pathway, its high expression indicated better OS and RFS of BRCA.…”
Section: Discussionsupporting
confidence: 56%
“…Sonic hedgehog (SHH) release is controlled by glypicans, which stimulate its proteolytic processing into bioactive sonic hedgehog. Genes related to the hedgehog pathway have been shown to be associated with better survival of breast cancer patients (Kuehn et al 2021 ). Protein patched homolog 1 (PTCH1) serves as a receptor for SHH and associates with the smoothened protein (SMO) to transduce the hedgehog’s protein signals (Filmus and Capurro 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Since heparan sulfate proteoglycans modulate numerous signaling pathways relevant to cancer stem cell properties [ 7 , 25 ], we next used qPCR analysis to investigate the impact of SDC3 depletion on the expression of constituents of the notch pathway ( Notch1 , Hes1 , Hey2 , Msi1 , Msi2 ), hedgehog signaling ( SHH , PTCH1 , Gli1-3 , Robo1 ), Wnt signaling ( Wnt3A , Wnt 5A , SFRP1 , TCF7L1 , TCF7L2 ), and markers of epithelial-to-mesenchymal transition (EMT) ( Twist , Snail , CDH1 , Vimentin , ZEB1 ) by SKOV3 and CAOV3 cells. Moreover, we evaluated the expression of the other members of the syndecan family ( SDC1 , SDC2 , SDC4 ) for potential compensatory expression changes, and assessed the expression of the proto-oncogene tyrosine-protein kinase Src, previously described to interact with Sdc3 [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…In line with our analysis, various studies show the correlation between heparan sulfate proteoglycans and stemness-related signaling [ 7 , 22 , 39 , 50 ]. For example, increased 3-O-sulfation of heparan sulfate enhances expression of the Wnt-dependent transcription factor TFF4/TCF7L2 and 3D sphere formation in breast cancer cells and results in differential expression of constituents of the prognostically relevant hedgehog pathway [ 21 , 25 , 51 ]. Altered 3-o-sulfation of heparan sulfate has also been shown to sensitize ovarian carcinoma to oncogenic signals and to be a predictor of prognosis [ 50 ].…”
Section: Discussionmentioning
confidence: 99%